2000
DOI: 10.1029/2000jc900045
|View full text |Cite
|
Sign up to set email alerts
|

On modeling the anisotropic failure and flow of flawed sea ice

Abstract: Abstract. The failure and flow of sea ice on scales small and large is characterized by the propagation of oriented leads and cracks. In this paper a theory for the dynamical treatment of anisotropic oriented flaws in sea ice is developed and used to examine the interaction of these oriented flaws under idealized stress forcing. The essential idea of the theory is to take one or more oriented weak leads imbedded in thick ice. A constitutive law for both the thin and thick ice is taken to be similar to laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 35 publications
3
141
0
Order By: Relevance
“…This relationship between continuum-scale and subcontinuum scale ice strength is useful in extrapolating from laboratory-determined estimates of P* [e.g., Sammonds et al, 2005]. The continuum, lemon-shaped plastic yield curve may be considered to be an alternative to commonly-adopted yield curve shapes, such as the ellipse [Hibler, 1979], Coulombic ice-cream cone [Tremblay and Mysak, 1997] or modified Coulombic ellipse [Hibler and Schulson, 2000].…”
Section: Continuum Gcm-scale Rheology Derived From Ensemble Averagingmentioning
confidence: 99%
See 4 more Smart Citations
“…This relationship between continuum-scale and subcontinuum scale ice strength is useful in extrapolating from laboratory-determined estimates of P* [e.g., Sammonds et al, 2005]. The continuum, lemon-shaped plastic yield curve may be considered to be an alternative to commonly-adopted yield curve shapes, such as the ellipse [Hibler, 1979], Coulombic ice-cream cone [Tremblay and Mysak, 1997] or modified Coulombic ellipse [Hibler and Schulson, 2000].…”
Section: Continuum Gcm-scale Rheology Derived From Ensemble Averagingmentioning
confidence: 99%
“…This rheology is appropriate to sea ice treated as a continuum on a large scale, e.g. 100 km, but it has also been suggested that this rheology is appropriate as a description of the material behavior of sea ice on much smaller, laboratory, scales [e.g., Hibler and Schulson, 2000], although with a slightly modified ice strength and yield curve aspect ratio. For this reason, we consider a material rheology given by the elliptic yield curve and flow rule described in Hibler and Schulson [2000], which allows the possibility of tensile stress.…”
Section: A1 Elliptic Yield Curvementioning
confidence: 99%
See 3 more Smart Citations